Pengaruh Motivasi Kerja dan Disiplin Kerja di Unit Pelaksanaan Teknis Pengawasan Ketenagakerjaan Kota Batam Dinas Tenaga Kerja dan Transmigrasi Provinsi Kepulauan Riau - Ovia Qadarsiki; Rahmat Hidayat; Ayuning Budiati (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the influence of work motivation and work discipline on employee performance at the Batam City Manpower Supervision UPT. Using a descriptive quantitative approach with a survey method, this study involved 70 respondents through a saturated sampling technique. Data were collected through observation, interviews, documentation, and Likert scale questionnaires. The validity and reliability of the instrument were tested using the construct validity and composite reliability methods with the help of Partial Least Square (PLS) analysis. The results showed that all variables had very good validity and reliability, with outer loading values> 0.6, composite reliability> 0.600, and no collinearity problems (VIF <5.00). Hypothesis testing showed that work motivation (p = 0.037) and work discipline (p = 0.000) had a significant effect on employee performance. Work discipline had the most dominant influence on performance. This finding emphasizes the importance of strengthening motivation and discipline in order to improve the performance of civil servants in the employment sector.  Keywords: Work Motivation, Work Discipline, Employee Performance, PLS-SEM